Interpersonal Meaning in a Social Media Chat Mood Analysis - Anneke Lineke Warouw (Budapest International Research and Critics University, 2022)
Clauses as exchange are interesting to discuss because they contain interpersonal meanings that always occur in communication between language speakers. This research aimed to analyze the mood clauses and its elements. The research used a qualitative descriptive method with the approach on systemic functional grammar introduced by Halliday (2014) The source of data taken from The Ellen Show program in YouTube with the topic “Bill Gates chats with Ellen For the First Time.” This was dialogue between Bill Gates and the host of the program, Ellen, on February 21, 2018. The results show that the types of mood clause or interpersonal meaning found in the chat between Bill Gates and Ellen in Ellen Show program are declarative (98 mood clauses), negative (10 mood clauses), polar question (8 mood clauses), and WH-question (3 mood clauses). The other elements called residue that accompany the mood clause are complement, predicator, and adjunct. Declarative mood type is very dominant in the dialogue. In other word, the function of the mood clause in the dialogue is to give information about someone’s life, in this case the life of Bill gates and his experiences and achievements to come to success. Moreover, it also gives inspiration to all the audiences that good achievement comes from great effort.